1998
DOI: 10.1002/(sici)1521-3773(19981231)37:24<3397::aid-anie3397>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Model of Cytochrome c Oxidase: Thermodynamic Implications

Abstract: The environment of the Cu ion in the distal ligand group decides the fate of the reduction of O by the two analogues 1 and 2 of the heme a Cu center in cytochrome c oxidase. The fourfold coordination by N in 1 favors the Cu oxidation state and leads to a 4 e -4 H reduction and the formation of H O under physiological conditions, while with 2 a 2 e -2 H reduction occurs to form the cytotoxic H O .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…With the use of binuclear Fe II -Cu I complexes 9 and 10 (Figure ), Collman and co-workers demonstrated that the state of the bound peroxo was very sensitive to the nature of the Cu I -coordinating site. Complex 9 predominately catalyzes the two-electron reduction of O 2 to H 2 O 2 , whereas 10 catalyzes the four-electron reduction of O 2 to H 2 O under physiological conditions . The 4e – ORR with catalysts on the graphite disk electrode can be written as eqs –. …”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of binuclear Fe II -Cu I complexes 9 and 10 (Figure ), Collman and co-workers demonstrated that the state of the bound peroxo was very sensitive to the nature of the Cu I -coordinating site. Complex 9 predominately catalyzes the two-electron reduction of O 2 to H 2 O 2 , whereas 10 catalyzes the four-electron reduction of O 2 to H 2 O under physiological conditions . The 4e – ORR with catalysts on the graphite disk electrode can be written as eqs –. …”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…Proposed energy diagram of O 2 reduction and the relative energy changes in the four-electron vs two-electron reduction of O 2 . Redrawn with permission from ref . Copyright 1998 Wiley-VCH.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…Several synthetic model complexes have been developed to mimic the c NOR active site. Some of the first mimics for c NORs were model complexes that were originally designed for heme-copper oxidases, and the Cu was subsequently replaced by a non-heme Fe center. ,, The first heme/non-heme diiron dinitrosyl complex was synthesized by Karlin and coworkers, using a TPP 2– derivative for the heme, with a covalently-linked TMPA (tris­(methylpyridyl)­amine) ligand to mimic the Fe B site (see Figure , left) . While this complex was able to generate a diferrous dinitrosyl complex, it was not able to catalyze the reduction of NO to N 2 O .…”
Section: The Nitrogen Cyclementioning
confidence: 99%
“…In addition to spectroscopic studies, the stoichiometric reactivity of these species toward exogenous reductants, acid sources, and hydrogen atom donors (H + + e – ) has been evaluated to gauge their reactivity properties. The electrocatalytic O 2 -reduction with heme–Cu catalysts in fact has proven to be very successful, especially from the systematic studies carried out by Collman and co-workers. ,,,, Insights can and have probed aspects such as the role of the Cu ion, pH effects, solvent polarity influences, and how rates of electron flux (from an electrode) govern O 2 -reduction efficiency.…”
Section: Small Molecule Synthetic Models Of Heme-copper Oxidasesmentioning
confidence: 99%